Relatório de estágio curricular supervisionado em medicina veterinária - (:unkn) unknown (Universidade Federal do Pampa, 2017)
This report aims to describe the activities carried out by the academic, during the period of the Supervised Curricular Internship in Veterinary Medicine and to report a clinical case of interest. The internship was carried out in the area of clinic and surgery of small animals, from August 17 to November 17, 2017, under the guidance of prof. Dr. Mauren P. Emanuelli. The total workload of 540 hours was fulfilled, of those 450 carried out in practical activities and 90 in the preparation of the ECSMV report. The place chosen for the internship was the clinic Dogs and Cats Camobi, located in Santa Maria - RS, because it is a traditional clinic in the city. It was possible for the intern to follow clinical consultations, perform outpatient procedures and assist in surgical procedures, putting into practice the technical knowledge acquired during graduation.
Report of supervised internship in veterinary medicine
Keywords: Medicina veterinária; Clínica médica veterinária; Clínica de pequenos animais; Cirurgia veterinária; Cirurgia de pequenos animais; Veterinary medicine; Veterinary medical clinic; Small animal clinic; Veterinary surgery; Small animal surgery; CNPQ::CIENCIAS AGRARIAS